Do work-life balance practices mediate in the relationship between female participation and financial performance? - María Dolores Odriozola; Elisa Baraibar-Diez (European Journal of Management and Business Economics (EJM&BE), 2018)
Purpose: The purpose of this paper is to analyse the relationship between the participation of women in companies with financial performance. However, this relationship does not arise directly. The authors argue that the participation of women in the company's staff has a positive effect on the creation of work-life balance (WLB) practices, due to women have traditionally assumed family responsibilities, and subsequently these practices positively affect financial performance. WLB practices are a tool to balance employees' professional and personal goals. Design/methodology/approach: This study aims to determine whether WLB practices mediate in the relationship between female participation in the workforce and financial performance on large companies listed in the Spanish Stock Exchange Index during the period from 2008 to 2013. Findings: The main finding is that female participation in the workforce positively affects to the availability of WLB practices, but WLB practices are not a mediator to increase financial performance. Originality/value: The study is a new contribution for academics and practitioners, since the WLB has a role of moderating variable; and the positive joint effect of female participation and WLB practices is tested over the company's outcomes, instead of over the individual employee behaviour like in previous literature. In addition, this effect is studied in a country with economic recession where corporate WLB practices have increased in the last decade.
Keywords: M40; 650; Mediation; Financial performance; Female workforce; Work-life balance